PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK MATA PELAJARAN IPAS KELAS V SDN 32 CAKRANEGARA TAHUN PELAJARAN 2024/2025 - Nimala Dewi, RR. Wahyi; Husniati; Kemala Dewi, Nurul; Hasnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study addresses the persistently low critical thinking skills observed among fifth-grade students in IPAS (Science, Social, and Cultural Studies) at SDN 32 Cakranegara. This problem largely stems from teachers' frequent reliance on conventional, teacher-centered learning models. The research aimed to investigate the influence of the Problem-Based Learning (PBL) model on the critical thinking skills of fifth-grade IPAS students at SDN 32 Cakranegara. This study utilized an experimental approach with a Quasi-Experimental Nonequivalent Control Group Design. The population consisted of 60 fifth-grade students from SDN 32 Cakranegara, with 30 students in the experimental group and 30 in the control group. Data were collected using observation and tests specifically designed to measure students' critical thinking skills in IPAS. Research instruments underwent validity and reliability tests. Data collection techniques included observation sheets and critical thinking skills tests in the form of essays. Normality, homogeneity, hypothesis, and effect size tests were conducted. The hypothesis testing, performed using an independent samples t-test, yielded a significance value (2-tailed) of 0.001 ≤ 0.05. This result indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, demonstrating a significant influence of the Problem-Based Learning model on the critical thinking skills of fifth-grade IPAS students at SDN 32 Cakranegara. Therefore, the PBL learning model is recommended for implementation to measure and enhance critical thinking skills in elementary school students.